2016
DOI: 10.1364/oe.24.018799
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature continuous wave operation of InAs-based quantum cascade lasers at 15 µm

Abstract: We report low threshold InAs/AlSb quantum cascade lasers emitting near 15 µm. The devices are based on a vertical design similar to those employed previously in far infrared InAs-based QCLs, whereas the doping level of the active core is considerably decreased. The lasers exhibit a threshold current density as low as 730 A/cm2 in pulsed mode at room temperature and can operate in this regime up to 410K. The continuous wave regime of operation has been achieved in these devices at temperatures up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…InAs based QCL are also good candidates in particular for short wavelengths around 3 µm. More recently, Baranov and co-workers have demonstrated InAs / AlSb QCL emitting at 15 µm wavelength with a low threshold current density at room temperature [19]. The QCL developed within this work will be used for the chemical analysis in the 4 -10 µm wavelength range.…”
Section: Designmentioning
confidence: 92%
“…InAs based QCL are also good candidates in particular for short wavelengths around 3 µm. More recently, Baranov and co-workers have demonstrated InAs / AlSb QCL emitting at 15 µm wavelength with a low threshold current density at room temperature [19]. The QCL developed within this work will be used for the chemical analysis in the 4 -10 µm wavelength range.…”
Section: Designmentioning
confidence: 92%
“…As a result, they were able to obtain wavelengths as short as 2.63 -2.65 µm, operating at around 175 K [1]. Baranov's group reported that they achieved room temperature CW operation in InAs/AlSb based QCLs up to 15 µm [2] and 11 µm at 320 K [3], in 2016 and 2018, respectively. Those QCLs were the most recent InAs/AlSb reported before the writing of this thesis.…”
Section: Inas/alsb Based Qclmentioning
confidence: 99%
“…At low temperature, wavelengths as short as 2.63 -2.65 µm can be obtained from an InAs/AlSb based QCL [1]. At room temperature, continuous-wave (CW) operation was reported with wavelength up to 15 µm [2], while the highest CW operating temperature of 320 K was demonstrated for devices lasing at 11 µm [3]. The advantage of InAs/AlSb structure is its very large conduction band offset up to 2.1 eV and a large Γ-L distance of 0.73 eV in InAs [4].…”
Section: Introductionmentioning
confidence: 99%
“…Now, QCLs can generate high CW power output up to 5.1 W at room temperature, and cover the spectral range from 3 up to 300 µm by simple varying the material components. Broadband heterogeneous QCLs with the broad spectral range from 3 to 12 µm, wavelength agile QCLs based on monolithic sampled grating design, and on-chip beam QCL combiner are being developed for the next generation tunable mid-infrared source [3,4]. The far-IR (terahertz) QCLs are now presented by a new class of light sources with room temperature operation in the terahertz (THz) spectral range, with nearly 2 mW of optical power and significant tunability [5][6][7].…”
Section: Introductionmentioning
confidence: 99%